Application of Ethnobotanical indices on the Timli study area, Shivalik Range, Dehradun, Uttarakhand, India - Priya, P.; Santhanpandi, P.; Thakur, Ajay; Chittibabu, C.V. (Indian Forester, 2024)
The study aims to understand the utilization of plants in traditional medicine by the inhabitants of Timli study area located in the Shivalik Range, Dehradun, Uttarakhand, India. A semi-structured interview was conducted with a total of 115 informants with 89 men and 26 women between ages 20-70 were orally interviewed on the potent ethnomedicines of the study area, that represented 10% of the total family unit in the area. These ethnomedicines today guarantee our life against harmful chemicals that are regarded unsafe to living beings and their environment. People are looking into a more natural lifestyle for enhancing safety and security. Quantitative ethnobotany is concerned with determining the value of plants and vegetation to the local community. They are tools to quantify the recorded qualitative data in a Questionnaire survey. The parameters observed in this study include Fidelity Level (FL), Use Value (UV), Relative Frequency of Citation (RFC) and Informant Consensus Factor (ICF). Fidelity Level (FL), Use Value (UV) and Relative Frequency of Citation (RFC) were calculated for 19 medicinal herbs and the Informant Consensus Factor (ICF) for most cited ailments. The Shivalik habitat plays an important role in the growth and development of medicinal herbs and maintains the species diversity of the area. This study may also form a bridge between the local healers with researchers, to enhance the industrial potential of these ethnomedicines in the future to come. Though the local inhabitants would claim a high level of efficacy, there is a need for scientific standardization of the herb, their dosage and administering methods.